The mediating effect of organizational commitment and moderating role of strategic implementation in the relationship between high performance work practices and organizational performance - Muhammad, Ibrahim Garba (2017)
Many studies on strategy and strategic human resource management have utilized resource-based view to explain the process through which organizations can gain sustainable competitive advantage and improve their performance. This viewpoint has overlooked the important role of managers in structuring, bundling and leveraging organizational resources to create superior value for owners and customers. However, there is still limited attention to how such role can be utilized to determine the performance of banks in Nigeria. Specifically, the study investigated the mediating role of organizational commitment and the moderating role of strategic implementation on the effect of high-performance work practices on the performance of Nigerian banks. The study employed a cross-sectional design to collect data from 400 participants using mail and personally administered questionnaires. A total of 258 usable questionnaires were retrieved to test five hypotheses. The results of Partial least square structural equation modelling analysis revealed that extensive training and development, recruitment and selection, organizational commitment, and strategic implementation had a direct and significant effect on bank performance in Nigeria. The study did not show a direct effect of job security, empowerment, compensation, and performance appraisal. Furthermore, the study demonstrated an indirect effect of extensive training and development, compensation, recruitment and selection and performance appraisal through the mediating role of organizational commitment. In line with scholarly suggestion for incorporating a moderator in the organizational level relationship between organizational commitment and organizational performance, this study confirmed the moderating role of strategic implementation. The study also contributes to the literature on how resource management model contributes to resource-based view by integrating the role of managers. Finally, the study addresses a call for a reflective-formative assessment of organizational performance as a multifaceted construct, discusses the implications and limitations, and suggests areas for future research.